Optimal operation of a multi-energy system considering renewable energy sources stochasticity and impacts of electric vehicles - Ata, Mustafa; Erenoglu, Ayse Kubra; Sengor, Ibrahim; Erdinc, Ozan; Tascikaraoglu, Akin; Catalao, Joao P. S. (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Electrical, heating and cooling energy demands of the end users are increasing day by day. For the sake of using fewer fossil fuels, decreasing the energy costs and gas emissions as well as increasing the efficiency and flexibility of the traditional energy systems, multi-energy systems (MESs) have begun to be used. In this study, a MES structure which also includes renewable-based generation units as suppliers together with combined heating and power (CHP) and heat pumps (HPs) is presented. The proposed MES structure is modelled as a mixed integer linear programming (MILP) problem with the objective of minimizing total gas and electricity costs in daily operation. Furthermore, electric vehicles (EVs) as a new type of electrical load with inherently different characteristics are evaluated considering different end-user types as residential and commercial together with the capability of offering operational flexibility. In order to tackle with the intermittent structure of the renewable energy sources, a scenario oriented stochastic programming concept is taken into account by addressing real radiation, temperature, and wind data. Moreover, actual time-of-use (TOU) tariffs for electricity prices along with the real gas prices are evaluated. The simulation results of the devised model are given for different case studies and the effectiveness of the system is demonstrated via a comparative study. As a result, it is found that the operational costs are decreased nearly 5.49% by integrating only photovoltaic (PV) production according to the case which has no additional sources. Also, a substantial reduction of 13.45% is achieved by considering both PV and wind generation. Moreover, the flexibility is increased with taking EVs into account on the demand side and this leads to a cost reduction of 8.81% even if EVs are integrated to the system as an extra load. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Electric vehicles; Energy costs; Heating and cooling; Multi energy systems; Renewable energy sources; OPTIMIZATION; STORAGE; MANAGEMENT; SIMULATION; DEMAND; DESIGN; HUB; Thermodynamics; Energy & Fuels